Sarajevo and its Satellites - Dijana Alić (Docomomo Journal)
In 1942, Grabrijan and Neidhardt guest-edited an issue of the Croatian architectural journal Technical Gazette (Tehnički Vjesnik). Titled Sarajevo and Its Satellites (Sarajevo i njegovi trabanti), the publication contributed to architectural and urban debates and to the development of the regulatory urban plan of the city of Sarajevo. It allowed the authors to present their design work and writings–both individually and collaboratively–framed by their shared vision of a new master plan for the city. This paper argues that despite the authors’ interest in and fascination with the historic core of Sarajevo, their master plan denied the relevance of the existing urban fabric to the growing city. Their discussion of the old precinct demonstrates the authors’ gradually shifting intentions as they abandon their search for modernity within the old fabric’s authentic qualities. Instead, they associated Islamic urban forms with stereotypical and preconceived oppositional relationships between new and old, progressive and backward. As this paper demonstrates, the result of this approach was that Grabrijan and Neidhardt’s master plan assigned only a peripheral role to the old precinct within their proposed vision. However, even within this publication, some projects, such as designs of mining workers’ housing, anticipate Neidhardt and Grabrijan’s later redefinition of Bosnian architecture as innately modern, which would become a major theme of their subsequent collaboration and well-known book, Architecture of Bosnia and the Way towards Modernity, published 15 years later in 1957.